Desk Research on Pollutants for Ecofriendly Environmental Researchers - R. Hema; S. Sajitha; S. Subbulakshmi; T.R. Vijayaram; M. Sundararajan (International Journal of Environmental Noise and Pollution Control, 2024)
Substances of foreign origin called pollutants, play a main part in alarming health hazards. The essentiality of water is being used without considering the dreadful contaminants. Arsenic, the most potential and dreadful element, is always ignored whenever there is a need for the purification of water for drinking. Rehabilitation of any affected area in view of health issues is highly mandatory as per the international provisions of Environmental legislation. In this work, we have tried to identify the potential pollutants, their sources, and contamination limits toward hazardous health effects.
Keywords: Pollutants; acidity and alkalinity; inorganic; organic; toxicants; turbidity